Determinants of digital bank transformation: a systematic literature review with prisma and bibliometrics - Avianto, Wahyu; Siregar, Hermanto; Ratnawati, Anny; Siregar, Mulya E (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
In response to emerging financial technology (fintech) that might disrupt the banking industry, several financial institutions are undergoing digital transformation. Banks are increasingly integrating digital strategy into their business planning rather than adding it on. This research aims to identify the determinants that influence digital bank transformation. The research was conducted through a systematic literature review of 364 published papers using PRISMA and bibliometric approaches. This method is commonly used in various fields, including medicine, psychology, social sciences, and more, to provide a comprehensive and impartial summary of the current state of knowledge on a particular subject. The approach used in this systematic literature review method is the PRISMA approach. The results of the literature review show that there is an increasing trend of research related to digital banks from 2015 to 2023, which is in line with the trend of digitalization in the banking industry in both developed and developing countries. The analysis is deepened to see the important factors influencing digital bank transformation. The determinants in the digital bank transformation process include the level of digitalization, application user growth, IT investment, IT committee, cyber security, and ecosystem stocks. The results of this literature review will be a reference for further research related to digital banks, in line with the rapid digital transformation process in banking.